Diabetes mellitus. Some necessary considerations - Idalia Murillo Sevillano (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Diabetes mellitus has become a public health problem worldwide, due to the burden it supposes for health services. In this article, some aspects which influence the increasing of the disease incidence, some related to not modifiable risk factors as age, sex, skin color and other which are modifiable such as socio-economical conditions schooling, obesity, physical inactivity and diet. In addition, the role of the programs for the diabetic patient attention, as a strength for preventing secondary complications of the disease.